Integration of SOLE-Based Progressive Web Apps: Trends and Empirical Insights for Critical Thinking in Education - Amir Rofiudin; Hakkun Elmunsyah; Muhammad Aris Ichwanto (Universitas Muhammadiyah Mataram, 2025)
Digital education expands rapidly, yet research on Progressive Web Apps (PWA) and Self-Organized Learning Environments (SOLE) often proceeds separately, obscuring how integration with standardized critical-thinking measures improves learning. This review addresses that gap by synthesizing evidence, specifying how PWA affordances scaffold SOLE processes, and offering guidance for practice and policy. A Systematic Literature Review (SPAR-4-SLR) was conducted. Searches in Scopus, SINTA, and Google Scholar covered 2020–2025 using Boolean strings (PWA and SOLE and “critical thinking”). Inclusion targeted peer-reviewed studies in formal education reporting learning or critical-thinking outcomes; screening followed PRISMA 2020. Instruments comprised a four-criterion Likert quality appraisal (objectives clarity, methodological appropriateness, data quality and completeness, educational relevance; cutoff ≥ 12), a standardized data-extraction form, and NVivo 12 for thematic analysis with calibration and inter-rater agreement (Cohen’s κ ≥ 0.70). Twenty-five studies were included. Results show 32% focused on PWA (flexibility, motivation, project-based engagement), 40% on SOLE (independence, collaboration, inquiry), and 28% on integrated approaches indicating potential for adaptive, participatory, contextual ecosystems, although instruments are heterogeneous and causal designs limited. Theoretically, the review specifies a technology–pedagogy alignment that maps offline access, installability, responsiveness, and notifications to SOLE phases and core critical-thinking dimensions. Practically, it recommends a design checklist for educators, rubric and outcome alignment for curriculum developers, and policies prioritizing device access, reliable connectivity with offline options, lightweight authentication, and professional development for SOLE facilitation.